Arduino-based Disaster Management System - Beltran Jr., Angelo; Dizon, Keith Joseph; Nones, Kristina; Salanguit, Reina Louise; Santos, Jay Bhie; Santos, Josemaria Rei (Universitas Muhammadiyah Yogyakarta, 2021)
The Philippines suffered from an inexhaustible number of deadly typhoons, earthquakes, volcano eruptions making it a country prone to natural disasters. Natural causes are inevitable but having a warning device to alert people and prepare them from what’s about to come is essential today. In this paper, the Arduino-based disaster management system is proposed. The device created is a disaster management device that consists of temperature, soil drift, accelerometer, tilt, and rain sensor. A hardware prototype model was developed. It is operated through microcontroller Arduino and implemented using the C language. The effectiveness of the proposed method is verified by experimental studies. If a sensor is activated, it will send data to the selected receiver, which is a mobile phone. Acquired data were provided in this article. Results reveal the effectiveness and efficacy of the proposed system. An expressive future directive has been incorporated at the end of this paper.